Diffuse Hepatic and Spleen Uptake of Tc-99m MDP on Bone Scintigraphy Resembling Liver-Spleen Scintigraphy in a Patient of Plasma Cell Tumor - Mohammad Reza Ravanbod; Reza Nemati; Hamid Javadi; Iraj Nabipour; Majid Assadi (Case Reports in Radiology)
The present case demonstrates a diffuse intense hepatic and, to a lesser degree, spleen, Tc-99m MDP uptake on a routine bone scintigraphy resembling liver-spleen imaging. A 49-year-old female with a history of anaplastic plasma cell tumor and suffering from bone pain was referred for bone scintigraphy to evaluate possible bone metastases. The bone scintigraphy showed diffuse hepatic and spleen uptake of Tc-99m MDP resembling liver-spleen imaging. Furthermore, bone uptake of Tc-99m MDP was significantly diminished and there were no abnormal foci throughout the skeleton. The bone scintigraphy of the present case of an anaplastic plasma cell tumor suggests the possible presence of amyloidosis.